Pengaruh Pop Up Book Dalam Mengenalkan Huruf Alphabet Di Taman Kanak-Kanak Bhakti Bunda Padang - Inda Hayati, Fithri; Yeni, Indra (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
The purpose of this article is to disuss the results of research on how much influence Pop Up Books have in introducing letters of the alphabet at Bhakti Bunda Padang Kingdergarten. In the introduction of alphabet letters, they have not used Pop Up Book media and learning still seems monotonous. As a result, shildren are less interested and respond during learning. This is because the media used in learning is only blackboards and letter cards. This research is a quantitative research using Quasi Experiment method. The population in this study were all students of Bhakti Bunda Padang Kingdergarten with the Cluster Sampling technique (area sampling) namely selecting or taking samples based on certain characteristic needed in the study. Based on the data above, the classes that will be used as samples are classes B1 and B3 where groups B1 and B3, taking into account the homogeneity of the same children aged 5-6 years and the same learning facilities.Based on the hypothesis test table in the sig column. (2-tailed) obtained a sig value of 0.024. this value indicates that the sig value is 0.024 <0.05. in accordance with the measurement criteria in the hypothesis test, if a sig value <0.05 is abtained, it can be concluded that there is a significant effect of Pop Up Books in introducing alphabet letters in Bhakti Bunda Padang Kingdergarten.